Creativity and Rationale Enhancing Human Experience by Design - Carroll, John M.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Creativity and rationale comprise an essential tension in design. They are two sides of the coin; contrary, complementary, but perhaps also interdependent. Designs always serve purposes. They always have an internal logic. They can be queried, explained, and evaluated. These characteristics are what design rationale is about. But at the same time designs always provoke experiences and insights. They open up possibilities, raise questions, and engage human sense making. Design is always about creativity. Creativity and Rationale: Enhancing Human Experience by Design comprises 19 complementary chapters by leading experts in the areas of human-computer interaction design, sociotechnical systems design, requirements engineering, information systems, and artificial intelligence. Researchers, research students and practitioners in human-computer interaction and software design will find this state of the art volume invaluable.
Creativity and Rationale: The Essential Tension -- Critical Conversations: Feedback as Creativity in Software Design -- A Micro View of Design Reasoning: Two-Way Shifts between Embodiment and Rationale -- Evaluating Creativity -- Integrating Design Representations for Creativity -- Achieving both Creativity and Rationale: Reuse in Design with Images and Claims -- Predecessor Artefacts: Evolutionary Perspectives on a Reflective Conversation with Design Materials -- The PRInCiPleS Design Framework -- Using Rationale to Assist Student Cognitive and Intellectual Development -- Does Design Rationale Enhance Creativity? -- Promoting Group Creativity in Upstream Requirements Engineering -- Supporting Awareness in Creative Group Work by Exposing Design Rationale -- Studying Humans to Inform Interactive Narrative Technology -- Improvisation in the Cloud: Devised Theatre in Support of Problem-Finding -- The Practice Level in Participatory Design Rationale: Studying Practitioner Moves and Choices -- Managing Conflict in Information System Design Stakeholder Conferences: The role of Transparency Work -- Mining Creativity Research to Inform Design Rationale in Open Source Communities -- Creativity Meets Rationale: Collaboration Patterns for Social Innovation -- Patterns for Emergent Global Intelligence -- Collaborative Design Rationale and Social Creativity in Cultures of Participation -- Index.
Keywords: Computer science; Software engineering; Computer Science; User Interfaces and Human Computer Interaction; Media Design; Computer Applications; Software Engineering